(3MGTjI Ydi TQM edNU GdLZejfi dbGVi RGOg GdQheis - (3YHO GdYdj Hf eMeO Hf MSjf GdHQLfOj GdMfaj,J (B932 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdeTGQb hGdeZGQH hHYO , agPg JYdjbGJ Ydi GdehGVY GdeTcdI , hJfHjgGJ Ydi GdQehR hGdeHGMK GdNajI GdeYVdI efTQM GdedNU ai GdgjFI GdefShH GdeTJgQ HGdbGVi GdQhei s
(3BNQgG (B:s
(3JKHJ GdeWGHbI Ydi GdJMbjb dGjNQLg Edi GdJbQjH ceG dGjNai Ydi GdeJCed aYdjc HeWGdYI aEfg dGjNai Ydi cKjQ ef Phi GdCagGe Je s
(3HgG CTcGds
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3jJab ChdgG eY Chd GdfSNI GdChdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B172 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B586s
Keywords: (3Gdadcs